Anisotropic rare earth sintered magnet and its manufacturing method

An anisotropic rare earth sintered magnet with a ThMn12 main phase and R-rich/R(Fe,Co)2 grain boundary phases addresses phase segregation issues, achieving high coercive force and magnetic anisotropy through optimized composition and manufacturing methods.

JP7607637B2Active Publication Date: 2024-12-27SHIN ETSU CHEMICAL CO LTD

Patent Information

Application Number
JP2022510028
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-26
Filing Date
2021-03-18
Publication Date
2024-12-27
Estimated Expiration
2041-03-18

AI Technical Summary

Technical Problem

Existing anisotropic rare earth sintered magnets face challenges in forming stable grain boundary phases, which affect magnetic properties due to phase segregation at grain boundaries, making it difficult to achieve high coercive force and magnetic anisotropy.

Method used

The development of an anisotropic rare earth sintered magnet with a ThMn12 main phase and R-rich phase and R(Fe,Co)2 phase at grain boundaries, stabilized by specific element compositions and manufacturing methods such as two-alloy and grain boundary diffusion, ensuring phase equilibrium and enhanced magnetic properties.

Benefits of technology

The magnet exhibits high coercive force and magnetic anisotropy, with a coercive force of 5 kOe or more and a temperature coefficient of -0.5%/K or more, suitable for high-temperature applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007607637000001
    Figure 0007607637000001
  • Figure 0007607637000002
    Figure 0007607637000002
  • Figure 0007607637000003
    Figure 0007607637000003
Patent Text Reader

Abstract

An anisotropic rare-earth sintered magnet according to the present invention has a composition represented by formula (R1-aZra)x(Fe1-bCob)100-x-y(M1 1-cM2 c)y (R is at least one selected from among rare earth elements and has Sm as an essential component, M1 is at least one element selected from the group consisting of V, Cr, Mn, Ni, Cu, Zn, Ga, Al, and Si, M2 is at least one element selected from the group consisting of Ti, Nb, Mo, Hf, Ta, and W, and x, y, a, b, and c satisfy 7≤x≤15 atomic% and 4≤y≤20 atomic%, 0≤a≤0.2, 0≤b≤0.5, and 0≤c≤0.9, respectively), and is characterized by having at least 80% by volume of a main phase which has an average crystal grain size of at least 1 μm and is formed of a compound of a ThMn12-type crystal, and by having an R-rich phase and an R(Fe,Co)2 phase on a grain boundary portion. A method for producing an anisotropic rare-earth sintered magnet according to the present invention is characterized by pulverizing an alloy containing a compound phase of a ThMn12-type crystal, powder-molding the alloy in a magnetic field to form a compact, and then sintering the compact at a temperature of 800-1,400°C. According to the present invention, an anisotropic rare-earth sintered magnet having a compound of a ThMn12-type crystal as a main phase and exhibiting good magnetic characteristics and a method for producing the same can be provided.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing ThMn 12 The present invention relates to an anisotropic rare earth sintered magnet having a main phase of a compound of a type crystal, and a method for producing the same. [Background technology]

[0002] Rare earth magnets, especially Nd-Fe-B sintered magnets, are becoming increasingly popular due to the electrification of automobiles and Due to the trend towards higher performance and lower power consumption in industrial motors, demand is expected to grow and production volume is expected to increase further. However, there are concerns that the supply and demand balance of rare earth raw materials may be disrupted in the future, and in recent years, research into reducing the amount of rare earth used in rare earth magnets has been attracting attention. 12 The compound with the type crystal structure is RFe 14 Since it has a lower rare earth content than B compounds and has good magnetic properties, it is being actively researched as a next-generation magnet material.

[0003] For example, in Patent Document 1, ThMn 12 A permanent magnet made of an alloy containing a hard magnetic phase and a nonmagnetic phase with a tetragonal crystal structure has been reported. It is shown that adding at least one element selected from Cu, Bi, Mg, Sn, Pb, and In to an intermetallic compound mainly consisting of rare earth elements and Fe precipitates a phase that has a lower melting point than the main phase and is nonmagnetic.

[0004] In addition, in Patent Document 2, a main phase and a grain boundary phase are included, and the main phase is ThMn 12A rare earth permanent magnet has been reported in which the RT compound has a cubic crystal structure (R is one or more rare earth elements with La as an essential element, and T is Fe, or Fe and Co, or an element in which a part of the Fe and Co elements is replaced with M (one or more elements selected from Ti, V, Cr, Mo, W, Zr, Hf, Nb, Ta, Al, Si, Cu, Zn, Ga, and Ge)), the grain boundary phase has a cubic crystal structure, and the La-rich phase σ with a La composition ratio of 20 at% or more accounts for 20% or more of the cross-sectional area. It is said that the inclusion of a non-magnetic cubic La-rich phase in the grain boundary portion provides magnetic separation between the main phases and reduces the interface strain between the grain boundary phase and the main phase.

[0005] In Patent Document 3, ThMn 12 The main phase has a crystal structure of the SmFe type. 17 Rare earth magnets have been reported that have subphases including any of the Sm5Fe, SmCo5, Sm2O3, and Sm7Cu3 phases, with the volume fraction of the subphase being 2.3 to 9.5%. 17 The Sm2O3-based phase and SmCo5-based phase are magnetic phases that exhibit higher magnetic anisotropy than the main phase, and by isolating each of the crystal grains of the main phase and preventing the movement of domain walls within the main phase, the magnetization and coercivity of the magnet are improved. On the other hand, the Sm2O3-based phase and Sm7Cu3-based phase are non-magnetic phases, and by isolating each of the crystal grains of the main phase, the magnetization reversal of the main phase is prevented from propagating to the surroundings, improving the magnetization and coercivity of the magnet. It is also described that the Sm7Cu3-based phase is a non-equilibrium phase.

[0006] In Patent Document 4, an alloy having a main phase and one or more subphases and a composition of the entire alloy is R(Fe,Co). w-z Ti z Cu α (R is at least one rare earth element, 8≦w≦13, 0.42≦z<0.70, 0.40≦α≦0.70) A rare earth magnet alloy has been reported. It is also described that the subphase is mainly a crystalline phase with a Cu composition of 50 mol % or more of the entire subphase, and that the crystal structure of the subphase is KHg2 type.

[0007] In Patent Document 5, R x Fe100-x-y (V 1-a S a ) y (R is one or more rare earth elements including Y, x=5.5-18 atomic %, y=8-20 atomic %, a=0.05-0.7), and the main phase is ThMn 12 A rare earth permanent magnet with a body-centered tetragonal structure has been reported. The alloy is composed of a main phase and a rare earth rich phase, and is not considered to contain an RFe2 phase. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2001-189206 A [Patent Document 2] International Publication No. 2017 / 164312 [Patent Document 3] JP 2017-112300 A [Patent Document 4] JP 2019-044259 A [Patent Document 5] Japanese Patent Application Publication No. 06-231920 Summary of the Invention [Problem to be solved by the invention]

[0009] As mentioned above, ThMn 12 In order to obtain good magnetic properties in magnets having a main phase of this type compound, it has been proposed to form a structure consisting of a main phase and a grain boundary phase, as in Nd-Fe-B magnets, and non-magnetic phases such as La-rich phase (Patent Document 2) and R-Cu phase (Patent Documents 1 and 4) have been considered as the grain boundary phase. However, in reality, these phases segregate at grain boundary triple junctions and the like, making it difficult to form a grain boundary phase between two particles, and there has been a problem in that it is difficult to obtain a structure in which the surfaces of the main phase grains are covered by the grain boundary phase.

[0010] In addition, in Patent Document 3, a magnetic phase exhibiting high magnetic anisotropy, Sm5Fe 17The surface of the main phase grains is surrounded by the Sm5Fe or SmCo5 phase, and the magnetic domain walls are pinned by this phase, improving the coercive force. 17 The SmCo5 phase and the ThMn 12 Since it is difficult to achieve phase equilibrium with these type compounds, it is difficult to realize a structure in which the crystal grain surfaces of the main phase are surrounded by these phases.

[0011] On the other hand, in Patent Document 5, ThMn 12 An alloy consisting of a main phase and an R-rich phase has been proposed. However, since the composition range in which only two phases are formed in the R-Fe-V-Si quaternary system is extremely limited, it is difficult to reproducibly produce this structure.

[0012] The present invention has been made in view of the above problems, and provides a method for producing a ThMn alloy having excellent magnetic properties. 12 The object of the present invention is to provide an anisotropic rare earth sintered magnet having a main phase of a compound of the type crystal. [Means for solving the problem]

[0013] As a result of extensive research to achieve the above object, the present inventors have discovered that ThMn 12 The inventors have discovered that anisotropic rare earth sintered magnets having a main phase of a compound of this type crystal exhibit high coercivity when an R-rich phase and an R(Fe,Co)2 phase are present at the grain boundaries, and have completed the present invention.

[0014] Accordingly, the present invention provides the following anisotropic rare earth sintered magnet and method for producing the same. (1) The composition has the formula (R 1-a Zr a ) x (Fe 1-b Co b ) 100-x-y (M 1 1-c M 2 c ) y (R is one or more rare earth elements, Sm is essential, M 1 is one or more elements selected from the group consisting of V, Cr, Mn, Ni, Cu, Zn, Ga, Al, and Si; M 2is one or more elements selected from the group consisting of Ti, Nb, Mo, Hf, Ta, and W, and x, y, a, b, and c are each represented by 7≦x≦15 atomic %, 4≦y≦20 atomic %, 0≦a≦0.2, 0≦b≦0.5, and 0≦c≦0.9, respectively; 12 The anisotropic rare earth sintered magnet comprises 80 volume % or more of a main phase made of a compound of a Fe-type crystal, the main phase has an average crystal grain size of 1 μm or more, and contains an R-rich phase and an R(Fe,Co)2 phase at grain boundaries. (2) The anisotropic rare earth sintered magnet according to (1), characterized in that the R-rich phase and the R(Fe,Co)2 phase are contained in a total amount of 1% by volume or more. (3) The anisotropic rare earth sintered magnet according to (1) or (2), wherein the R-rich phase contains 40 atomic % or more of R. (4) The anisotropic rare earth sintered magnet according to any one of (1) to (3), wherein the R(Fe,Co)2 phase is a phase that exhibits ferromagnetism or ferrimagnetism at room temperature or above. (5) An anisotropic rare earth sintered magnet according to any one of (1) to (4), wherein the Sm / R ratio inside the main phase grains is lower than the Sm / R ratios of the R-rich phase and the R(Fe,Co)2 phase. (6) An anisotropic rare earth sintered magnet according to any one of (1) to (5), wherein the Sm / R ratio inside the main phase grain is lower than the Sm / R ratio in the outer periphery of the main phase grain. (7) The anisotropic rare earth sintered magnet according to (5) or (6), characterized in that the main phase grains do not contain Sm inside. (8) The anisotropic rare earth sintered magnet according to any one of (1) to (7), which exhibits a coercive force of 5 kOe or more at room temperature and has a temperature coefficient β of coercive force of -0.5% / K or more. (9)ThMn 12 The method for producing an anisotropic rare earth sintered magnet according to any one of (1) to (8), characterized in that an alloy containing a compound phase of a crystalline structure is pulverized, compacted in an applied magnetic field to form a green body, and then sintered at a temperature of 800°C or higher and 1400°C or lower. (10)ThMn 12The method for producing an anisotropic rare earth sintered magnet according to (9) above, further comprising crushing and mixing an alloy containing a compound phase of the type crystal and an alloy having a higher R composition ratio and Sm / R ratio than that of the alloy containing the type crystal compound phase, and compacting the powder under application of a magnetic field to obtain a green body. (11)ThMn 12 (9) or (10), characterized in that a material containing Sm is brought into contact with a sintered body having a compound phase of the type crystal as a main phase, and the Sm is diffused into the sintered body by heat treatment at a temperature of 600°C or higher and lower than the sintering temperature. (12) The method for producing an anisotropic rare earth sintered magnet according to (11), wherein the material containing Sm that is brought into contact with the sintered body is one or more selected from the group consisting of Sm metal, an alloy containing Sm, a compound containing Sm, and vapor containing Sm, and is in the form of one or more selected from the group consisting of powder, thin film, ribbon, foil, and gas. (13) The method for producing an anisotropic rare earth sintered magnet according to any one of (9) to (12), further comprising subjecting the sintered body to a heat treatment at a temperature of 300 to 900°C. Effect of the Invention

[0015] According to the present invention, ThMn 12 In an anisotropic rare earth sintered magnet having a main phase of a compound of this type crystal, it is possible to obtain an anisotropic rare earth sintered magnet that exhibits excellent magnetic properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The present invention relates to a magnet having a composition represented by the following formula: (R 1-a Zr a ) x (Fe 1-b Co b ) 100-x-y (M 1 1-c M 2 c ) y and ThMn 12 The main phase is a compound of the type crystal, ThMn 12The anisotropic rare earth sintered magnet contains 80% by volume or more of a main phase made of a compound of the type crystal, the average crystal grain size of the main phase is 1 μm or more, and contains an R-rich phase and an R(Fe,Co)2 phase at the grain boundaries. First, each component is explained below. Note that x, y, a, b, and c are 7≦x≦15 atomic %, 4≦y≦20 atomic %, 0≦a≦0.2, 0≦b≦0.5, and 0≦c≦0.9, respectively. The R-rich phase has a higher concentration of rare earth elements than the main phase. The R(Fe,Co)2 phase has a MgCu2 structure and is a compound phase known as a Laves phase. As such, the wide composition range makes it easy to produce the anisotropic rare earth sintered magnet of the present invention with good reproducibility.

[0017] R is one or more elements selected from rare earth elements, and Sm is essential. Specifically, R is essential for Sm, and may be a combination of Sm and one or more elements selected from Sc, Y, La, Ce, Pr, Nd, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu. R is the main phase of ThMn 12 It is an element necessary for forming a compound having a crystalline structure of the ThMn type. The content of R is set to 7 atomic % or more and 15 atomic % or less. It is more preferable if it is 8 atomic % or more and 12 atomic % or less. If it is less than 7 atomic %, an α-Fe phase precipitates and sintering becomes difficult, while if it exceeds 15 atomic %, it becomes difficult to sinter the ThMn 12 The volume ratio of the ThMn type compound phase decreases, and good magnetic properties cannot be obtained. 12 When R is Sm, the anisotropy field H A Therefore, Sm is essential for the anisotropic rare earth sintered magnet of the present invention. When there is no difference in Sm concentration between the inside and the outer periphery of the main phase grains, the amount of Sm contained in R is preferably 5% or more of R in atomic ratio, more preferably 10% or more, and particularly preferably 20% or more. By having the Sm ratio in this range, H A The effect of increasing the magnetic field becomes sufficient to obtain a high coercive force.

[0018] On the other hand, since Sm is less produced than Y, La, Ce, Pr, Nd, etc. and is limited in terms of resources, it is preferable to use Sm as effectively as possible. Therefore, a structure in which Sm is concentrated in the outer periphery of the main phase grains may be used to obtain high coercivity with a smaller Sm content. In the case where the structure has different Sm concentrations in the inside and outer periphery of the main phase grains, the Sm contained in R is preferably 0.1 atomic % or more and 50 atomic % or less of R in atomic ratio. It is more preferable that the Sm content is 0.2 atomic % or more and 40 atomic % or less, and particularly preferably 0.5 atomic % or more and 30 atomic % or less. It is more preferable that R is a combination of one or more elements selected from Y, La, Ce, Pr, and Nd and Sm.

[0019] Zr, ThMn 12 It has the effect of substituting R in the type compound to improve phase stability. The amount of Zr substituting R should be 20% or less of R in terms of atomic ratio. If it exceeds 20%, it becomes a ThMn 12 H type compounds A decreases, making it difficult to obtain high coercive force.

[0020] ThMn 12 It is known that in order for the crystalline structure to exist stably, a third element M is necessary in addition to the constituent elements R and Fe. 1 is one or more elements selected from the group consisting of V, Cr, Mn, Ni, Cu, Zn, Ga, Al and Si, and plays the role of the third element. 1 is the third element, M 2 Compared to Fe, ThMn is an element that tends to form compounds with R more easily than Fe, or tends to bond less easily with both Fe and R. One of the features of the anisotropic rare earth sintered magnet of the present invention is that in the magnet structure, the main phase ThMn 12 The difference between these two compounds is that they have R-rich and R(Fe,Co)2 phases at the grain boundaries, but they also contain M 1 By selecting the appropriate elements, it becomes easier to obtain a structure in which these three phases coexist stably. 1 and M. 2 If we combine these and write them as M, we get M 1The atomic ratio of M is at least 10% or more, preferably 30% or more, and more preferably 50% or more. 1 If the content of M is less than 10%, the R-rich phase among the above three phases is not formed stably. 1 and M. 2 The total of M is 4 atomic % or more and 20 atomic % or less. When M is less than 4 atomic %, ThMn 12 If the content exceeds 20 atomic %, the amount of heterophase formed increases and good magnetic properties are not obtained.

[0021] M 2 is one or more elements selected from Ti, Nb, Mo, Hf, Ta and W. 2 ThMn 12 It has the effect of stabilizing the M type crystal structure, but if it is contained in excess, 2 Carbides such as C phase and MgZn2 type compounds such as (Fe,Co)2M 2 The phase precipitates in the main phase and at grain boundaries. 2 The phase may have a composition richer than the stoichiometric composition, such as the Fe2Ti phase, and exhibit ferromagnetism, which adversely affects the magnetic properties of the sintered magnet. 1 Not including M 2 If only M is selected, the R-rich phase is unlikely to be formed stably. 2 In the case of a composition containing M, its content is at least 90% or less of M in terms of atomic ratio.

[0022] The anisotropic rare earth sintered magnet of the present invention is R, M 1 In addition, Fe is an essential constituent element. Furthermore, a part of Fe may be substituted with Co. The substitution with Co is 12 Curie temperature T of the compound c Increase the saturation magnetization M s The substitution rate of Co is set to 50% or less in atomic ratio. If the substitution rate exceeds 50%, M s On the other hand, the ratio of Fe and Co decreases. 1 and M 2However, in addition to the above, it may contain unavoidable impurities that are taken in from raw materials or mixed in during the manufacturing process, specifically H, B, C, N, O, F, P, S, Mg, Cl, Ca, etc. up to a total of 3% by weight.

[0023] Next, the phases that make up the anisotropic rare earth sintered magnet of the present invention will be described. The main phase in the anisotropic rare earth sintered magnet of the present invention is ThMn 12 R(Fe,Co,M) type crystal structure 12 It is preferable that elements such as C, N, and O, which are inevitably mixed in during the process of manufacturing sintered magnets, are not included in the main phase. However, if C, N, or O elements are detected in a composition analysis using an EPMA (electron probe microanalyzer) due to measurement variations, the method of preparing the observation sample, or the influence of the detection signals of other elements, it is considered that the H of the main phase A From the viewpoint of obtaining good results, the upper limit of each is preferably up to 1 atomic %. The average crystal grain size of the main phase is 1 μm or more, and preferably 1 μm to 30 μm. It is more preferable that it is in the range of 1.5 μm to 20 μm, and particularly preferably 2 μm to 10 μm. By setting the average crystal grain size in such a range, the residual magnetic flux density B due to the decrease in the degree of orientation of the crystal grains is reduced. r Decrease in coercive force H cJ The volume fraction of the main phase is good. r Or H cJ From the viewpoint of obtaining this, the content is 80% by volume or more, preferably 80% by volume or more and less than 99% by volume, and more preferably 90% by volume or more and 95% by volume or less, based on the total volume of the magnet. The average crystal grain size of the main phase is a value measured as follows. The cross section of the sintered magnet was polished to a mirror finish, then immersed in an etching solution (such as a mixture of nitric acid + hydrochloric acid + glycerin) to selectively remove the grain boundary phase, and the cross section was observed at random at 10 or more points using a laser microscope. The cross-sectional area of ​​each particle was calculated from the obtained observation images using image analysis, and the average diameter when these were regarded as circles was taken as the average crystal grain size. The volume fraction of the main phase is a value measured as follows. The structure of the anisotropic rare earth sintered magnet was observed and the composition of each phase was analyzed using an EPMA to confirm the presence of a main phase, an R-rich phase, and an R(Fe,Co)2 phase. The volume ratio of each phase was calculated as being equal to the area ratio in the backscattered electron image.

[0024] In order to effectively utilize Sm, the structure may be such that Sm is concentrated in the outer periphery of the main phase grains, and grains with a lower Sm concentration exist inside the main phase grains. In this case, the thickness of the high Sm outer periphery is not particularly limited, but from the viewpoint of obtaining a sufficient effect of suppressing the nucleation of reverse magnetic domains in the outer periphery of the main phase grains, and from the viewpoint of preventing the Sm content of the entire sintered body from becoming too high, the thickness is preferably 1 nm to 2 μm, and particularly preferably 2 nm to 1 μm. Such a form is obtained by increasing the Sm / R ratio (atomic ratio of Sm to R) in the R-rich phase or the R(Fe,Co)2 phase to the Sm / R ratio inside the main phase grains. It is more preferable if the structure does not contain Sm inside the main phase grains. In addition, some main phase grains with a uniform Sm concentration distribution may be included.

[0025] The R-rich phase and the R(Fe,Co)2 phase are formed in the grain boundary of the magnet structure. The grain boundary includes grain boundary triple junctions as well as grain boundary phases between two grains. Here, the R-rich phase is defined as a phase containing 40 atomic % or more of R. 1 It has been found that when the above composition containing the elements is used, it is easy to obtain a magnet containing three phases, namely, a main phase, an R(Fe,Co)2 phase, and an R-rich phase. For example, 1 In the case of Sm-Fe-Ti ternary sintered magnets that do not contain any elements, Sm(Fe,Ti) 12 There exists a composition region where the main phase, SmFe2, and Fe2Ti phases (excluding oxides, etc.) are in equilibrium, but Sm(Fe,Ti) 12 Since the main phase and the Sm-rich phase are difficult to equilibrate at low temperatures below 400°C, the Sm-rich phase does not form as a stable phase. 1 In the case of the Sm-Fe-V ternary system, where V is one of the elements, a Sm-rich phase with a high Sm concentration is formed, resulting in Sm(Fe,V) 12 A magnet containing three phases, SmFe2, Sm-rich phase, and Sm-rich phase, can be obtained. 1, M 2 In the Sm-Fe-V-Ti quaternary system, which contains both Sm(Fe,V,Ti) 12 Based on this knowledge, the anisotropic rare earth sintered magnet of the present invention uses a predetermined amount of M to form an R-rich phase and an R(Fe,Co)2 phase at the grain boundary. 1 A composition is selected that includes the elements.

[0026] The R-rich phase and the R(Fe,Co)2 phase have four main effects. The first effect is that they promote sintering. At the sintering temperature, both the R-rich phase and the R(Fe,Co)2 phase melt and become liquid phase, so liquid phase sintering proceeds and sintering is completed more quickly than in solid phase sintering when these phases are not present. In addition, when the R-rich phase and the R(Fe,Co)2 phase coexist, the liquid phase formation temperature tends to be lower than when only one of the phases is present, and liquid phase sintering proceeds more quickly.

[0027] The second effect is the cleaning of the main phase grain surfaces. Since the anisotropic rare earth sintered magnet of the present invention has a nucleation-type coercive force mechanism, it is desirable for the main phase grain surfaces to be smooth so that nucleation of reverse magnetic domains is less likely to occur. The R-rich phase and R(Fe,Co)2 phase are converted into ThMn 12 This cleaning effect suppresses the nucleation of reverse magnetic domains, which reduces the coercivity. In particular, the R(Fe,Co)2 phase is superior to other phases with R less than 40 atomic %, such as RM3, RM2, R(Fe,Co)M and R(Fe,Co)2M2, in that the R content is less than 40 atomic %. 12 It has a relatively high wettability with respect to the main phase and is easy to cover the surfaces of the main phase particles, so it has a large cleaning effect.

[0028] The third effect is the formation of grain boundary phases between two grains. In magnets containing R-rich phases in the structure, the adjacent ThMn phases can be formed by optimal sintering or aging treatment. 12Between the main phase grains of the ThMn type compound, a grain boundary phase containing more R than the main phase is formed. This weakens the magnetic interaction between the main phase grains, and the sintered magnet exhibits a high coercive force. 12 The compositional region in which only the two phases, the main phase of the ThMn-type compound and the R-rich phase, are in equilibrium is extremely limited, and considering the compositional variation, it is difficult to stably manufacture such magnets. 12 By making a magnet that contains three phases, namely, a R-type compound main phase, an R-rich phase, and an R(Fe,Co)2 phase, it is possible to stably form a structure in which the surfaces of the main phase grains are covered by the grain boundary phase between two particles. In addition, in a magnet that does not have an R-rich phase, it is difficult to form the grain boundary phase between two particles, or it is difficult for the grain boundary phase between two particles to cover the surfaces of the main phase grains, so it is difficult to obtain a magnet that exhibits sufficient coercivity.

[0029] The fourth effect is to increase the Sm concentration in the grain boundaries. When the grain boundary diffusion method is used as a manufacturing method to create a structure with different Sm concentrations inside and outside the main phase grains, the R-rich phase and R(Fe,Co)2 phase present in the grain boundaries become liquid phases during the diffusion process, and play a role in diffusing and penetrating the Sm placed on the sintered body into the interior. Therefore, the Sm / R ratio in at least either the R-rich phase or the R(Fe,Co)2 phase becomes higher than the Sm / R ratio inside the main phase grains. In addition, when the two-alloy method is used as a manufacturing method, the Sm concentration in the grain boundaries is increased by 100%. 12 By using an alloy mainly composed of a type compound phase and an alloy with a higher R composition ratio and Sm / R ratio than that of the type compound phase, the Sm / R ratio in at least one of the R-rich phase and the R(Fe,Co)2 phase of the sintered body becomes higher than the Sm / R ratio inside the main phase grains. As Sm is concentrated in the R-rich phase and the R(Fe,Co)2 phase, the Sm concentration in the outer shell of the main phase grains that contact these grain boundary phases also increases, and the H A This improves the coercive force of the sintered magnet.

[0030] As described above, the R-rich phase contains at least 40 atomic % of R. If the R content is less than 40 atomic %, the wettability with the main phase is insufficient, making it difficult to obtain the above-mentioned effects. It is more preferable to contain 50 atoms or more of R, and particularly preferable to contain 60 atoms or more of R. The R-rich phase may be an R metal phase such as the above-mentioned Sm phase, or an amorphous phase or an intermetallic compound with a high R composition and low melting point such as R3(Fe,Co,M), R2(Fe,Co,M), R5(Fe,Co,M)3, or R(Fe,Co,M). In addition, the R-rich phase may contain Fe, Co, M elements, and impurity elements such as H, B, C, N, O, F, P, S, Mg, Cl, and Ca up to a total of 60 atomic %.

[0031] On the other hand, the R(Fe,Co)2 phase is a Laves compound of MgCu2 type crystal, but when composition analysis is performed using EPMA or the like, taking into consideration measurement variations, etc., it is assumed that the R content is 20 atomic % or more and less than 40 atomic %. In addition, part of Fe and Co may be replaced by M element. However, the amount of M replacement must be within the range in which the MgCu2 type crystal structure is maintained.

[0032] The R(Fe,Co)2 phase in the anisotropic rare earth sintered magnet of the present invention is a magnetic phase. The magnetic phase here refers to ferromagnetism or ferrimagnetism, and has a Curie temperature T c RFe2 is a phase whose T is equal to or higher than room temperature (23℃) except for CeFe2. c is above room temperature, and if more than 10% of R in CeFe2 is replaced with other elements, T c On the other hand, except for GdCo2, T c is below room temperature or is a paramagnetic phase, but in the anisotropic rare earth sintered magnet of the present invention, the substitution atomic ratio of Co for Fe is 0.5 or less, so in most cases the R(Fe,Co)2 phase becomes a magnetic phase. Generally, soft magnetic phases contained in the structure often have a negative effect on magnetic properties, but in the anisotropic rare earth sintered magnet of the present invention, the R(Fe,Co)2 phase has a greater effect of cleaning the main phase grain surfaces and forming grain boundary phases between two particles, so it is believed that even the magnetic phase contributes to an increase in coercivity.

[0033] The total amount of the R-rich phase and the R(Fe,Co)2 phase is preferably 1% by volume or more, more preferably 1% by volume or more and less than 20% by volume. Furthermore, the total amount of the R-rich phase and the R(Fe,Co)2 phase is preferably 1.5% by volume or more and less than 15% by volume, and even more preferably 2% by volume or more and less than 10% by volume. By setting the total amount of the R-rich phase and the R(Fe,Co)2 phase in this range, the area of ​​contact with the main phase grains is secured, and the H cJ It is easy to achieve the effect of increasing the size. r The decrease in magnetic properties is also suppressed, making it easier to obtain the desired magnetic properties.

[0034] In addition, the anisotropic rare earth sintered magnet of the present invention may contain R oxides, R carbides, R nitrides, M carbides, etc., which are formed by the unavoidably mixed C, N, and O. From the viewpoint of suppressing deterioration of the magnetic properties, the volume ratio of these is preferably 10 volume % or less, more preferably 5 volume % or less, and particularly preferably 3 volume % or less.

[0035] It is preferable to have as few phases other than those mentioned above as possible. For example, R2 (Fe, Co, M) 17 Phase, R3 (Fe, Co, M) 29 If phases are present in the magnet structure, their formation amount should be less than 1 volume % each in order to suppress the effect on magnetic properties and the resulting decrease in coercivity. Also, in order to ensure a sufficient proportion of the main phase, it is preferable that the (Fe,Co)2M phase and RM3, RM2, R(Fe,Co)M, R(Fe,Co)2M2, each of which has an R content of less than 40 atomic %, be less than 1 volume %. The total amount of these phases is preferably 3 volume % or less. Furthermore, in order to prevent a significant decrease in magnetic properties, it is preferable that the α-(Fe,Co) phase is not included in the anisotropic rare earth sintered magnet of the present invention.

[0036] Next, the manufacturing method will be described. The anisotropic rare earth sintered magnet of the present invention is manufactured by powder metallurgy. First, to prepare the raw alloy, metal raw materials of R, Fe, Co, M, alloys, ferroalloys, etc. are used, and the composition of the sintered body finally obtained is adjusted to a predetermined value, taking into consideration the loss of raw materials during the manufacturing process. These raw materials are melted in a high-frequency furnace or an arc furnace to prepare the alloy. The molten metal may be cooled by casting, or may be made into thin pieces by strip casting. In the case of the strip casting method, it is preferable to adjust the cooling rate to prepare the alloy so that the average crystal grain size of the main phase or the average grain boundary interval is 1 μm or more. If it is less than 1 μm, the powder after fine pulverization becomes polycrystalline, and the main phase crystal grains are not sufficiently oriented in the magnetic field molding process, resulting in B. r If α-Fe precipitates in the alloy, it is necessary to remove the α-Fe and 12 The alloy may be subjected to a heat treatment so as to increase the amount of the type compound phase formed. The alloy may be an alloy of a single composition, or may be prepared by preparing a plurality of alloys of different compositions and mixing the powders in a post-process.

[0037] The above-mentioned raw alloy is coarsely pulverized into powder having an average particle size of 0.05 to 3 mm by mechanical pulverization such as a Braun mill or hydrogen pulverization. Alternatively, the HDDR method (hydrogen disproportionation desorption recombination method) used as a manufacturing method for Nd-Fe-B magnets may be applied. The coarse powder is then finely pulverized by a ball mill or a jet mill using high-pressure nitrogen to obtain powder having an average particle size of 0.5 to 20 μm, more preferably 1 to 10 μm. Before or after the fine pulverization process, a lubricant or the like may be added as necessary. Next, the alloy powder is molded using a magnetic field press while the easy axis of magnetization of the alloy powder is aligned in an applied magnetic field to obtain a powder compact. The molding is preferably performed in a vacuum, a nitrogen gas atmosphere, an inert gas atmosphere such as Ar, or the like to suppress oxidation of the alloy powder.

[0038] The step of sintering the powder compact is carried out in a sintering furnace in a vacuum or inert atmosphere at a temperature of 800°C to 1400°C. At temperatures below 800°C, sintering does not proceed sufficiently and a high sintered density cannot be obtained. At temperatures above 1400°C, the sintering temperature is too high, and the sintered density is too low.12 The main phase of the α-Fe-type compound decomposes and α-Fe precipitates. The sintering temperature is preferably in the range of 900 to 1300°C. The sintering time is preferably 0.5 to 20 hours, more preferably 1 to 10 hours. Sintering may be performed in a pattern in which the temperature is raised and then held at a constant temperature, or in order to refine the crystal grains, a two-stage sintering pattern in which the temperature is raised to a first sintering temperature and then held at a lower second sintering temperature for a predetermined time may be used. Sintering may be performed multiple times, or a spark plasma sintering method or the like may be applied. The cooling rate after sintering is not particularly limited, but it can be cooled to at least 600°C or less, preferably 200°C or less, preferably at a cooling rate of 1°C / min to 100°C / min, more preferably 5°C / min to 50°C / min. In order to improve the coercive force, an aging heat treatment at 300 to 900°C for 0.5 to 50 hours may be further performed. By optimizing the sintering and aging conditions according to the composition, powder grain size, etc., it is possible to obtain a high-temperature sintered product with a high coercive force. cJ The sintered body is then cut and ground into a specified shape, and magnetized to produce a sintered magnet.

[0039] On the other hand, examples of methods for producing an anisotropic rare earth sintered magnet in which there are main phase grains whose interior Sm / R ratio is lower than the Sm / R ratios of the R-rich phase and the R(Fe,Co)2 phase include the two-alloy method and the grain boundary diffusion method.

[0040] When using the two-alloy method, two types of raw material alloys with different compositions are prepared using metal raw materials, alloys, ferroalloys, etc. of R, Fe, Co, and M. Three or more types of alloys may be used. In this case, ThMn 12 It is preferable to combine alloy A, which is mainly composed of a type compound phase and has a relatively low Sm / R ratio, with alloy B, which has a relatively higher R composition ratio and Sm / R ratio, and adjust the average composition to a predetermined composition. These alloys are produced by casting or strip casting, and then pulverized. The process of mixing the alloy powders may be performed in a coarse powder state before fine pulverization, or after fine pulverization. The mixture is then molded and sintered to produce a sintered body. Aging heat treatment may be performed to improve the coercive force.

[0041] In the two-alloy sintered magnet, the composition of alloy A is mainly responsible for the formation of ThMn 12 The main phase is formed of a type compound, and the R-rich phase, R(Fe,Co)2 phase, and the outer shell of the main phase grains are formed mainly by the components of alloy B. Therefore, the Sm / R atomic ratio of the R-rich phase and R(Fe,Co)2 phase formed in the grain boundaries is higher than the Sm / R atomic ratio inside the main phase grains. In addition, some of the Sm in the grain boundary phase replaces R atoms in the surface layer of the main phase grains, forming a core-shell structure with different Sm concentrations between the grain surface and the inside, increasing the coercive force.

[0042] On the other hand, in the grain boundary diffusion method, a sintered body is first produced by the single alloy method or the two-alloy method in the same manner as described above. At this time, R in the sintered body composition may or may not contain Sm.

[0043] Next, the obtained sintered body is subjected to grain boundary diffusion of Sm. After cutting and grinding the sintered body as necessary, a diffusion material selected from compounds containing Sm, such as metals, alloys, oxides, fluorides, oxyfluorides, hydrides, and carbides, is placed on the surface in the form of powder, thin film, ribbon, foil, or the like. For example, a powder of the above material may be mixed with water or an organic solvent to form a slurry, which may be coated on the sintered body and then dried, or the above material may be placed on the surface of the sintered body as a thin film by means of vapor deposition, sputtering, CVD, or the like. The amount of the material to be placed is 10 to 1000 μg / mm 2 It is preferable that the concentration is 20 to 500 μg / mm 2 In this range, H cJ In addition, the increase in the production cost due to the high Sm content can be suppressed. In addition, by utilizing the property of high vapor pressure of Sm, Sm metal or Sm alloy may be heat-treated together with the sintered compact in the same chamber, and the Sm vapor may be brought into contact with the sintered compact.

[0044] The sintered body, with Sm placed on the surface, is heat-treated in a vacuum or in an inert gas atmosphere. The heat treatment temperature is preferably 600°C or higher and lower than the sintering temperature, and more preferably 700°C or higher and lower than 1100°C. The heat treatment time is preferably 0.5 to 50 hours, and more preferably 1 to 20 hours. The cooling rate after the heat treatment is not particularly limited, but is preferably 1 to 20°C / min, and more preferably 2 to 10°C / min. In order to improve the coercive force, an aging heat treatment may be further performed at 300 to 900°C for 0.5 to 50 hours.

[0045] The Sm placed on the sintered body penetrates into the interior of the sintered body while increasing the Sm concentration in the R-rich phase and the R(Fe,Co)2 phase during heat treatment, and the Sm / R ratio of these grain boundary phases increases. As the Sm concentration in the grain boundary phase increases, R atoms are replaced by Sm in the surface layer of the main phase grains that contact the grain boundary phase, and the Sm / R ratio in the surface layer of the main phase grains becomes higher than the Sm / R ratio inside the main phase grains, resulting in H cJ increases.

[0046] The anisotropic rare earth sintered magnet of the present invention thus produced has a residual magnetic flux density B of 5 kG or more at room temperature. r and a coercive force H of at least 5 kOe cJ Shows room temperature H cJ It is more preferable that the temperature coefficient of coercivity β is -0.5% / K or more. Here, β=ΔH cJ / ΔT×100 / H cJ (20℃)(ΔH cJ =H cJ (20℃)-H cJ (140°C, ΔT=20-140(°C)). The anisotropic rare earth sintered magnet of the present invention has a smaller change in coercive force with temperature compared to Nd-Fe-B sintered magnets, making it suitable for use at high temperatures. EXAMPLES

[0047] EXAMPLES The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0048] [Example 1] The composition was adjusted using Sm metal, electrolytic iron, Co metal, and V metal, and the alloy was melted in an Ar gas atmosphere using a high-frequency induction furnace, and then strip-cast on a water-cooled Cu roll to produce an alloy ribbon with a thickness of about 0.2 to 0.4 mm. The cross section of this alloy was polished and etched, and then the structure was observed using a laser microscope (Olympus Corporation, LEXT OLS4000). The observation points were located about 0.15 mm from the surface where the ribbon contacted the cooling roll, and 20 observations were performed. For each image, 20 lines parallel to the roll contact surface were drawn at equal intervals, and the intersections where these lines intersected with the grain boundary phase parts removed by etching were counted to calculate the average grain boundary phase interval, which was 3.6 μm. The alloy was subjected to hydrogen absorption treatment at room temperature, and then subjected to dehydrogenation treatment by heating at 400 ° C in a vacuum to produce coarse powder, which was then pulverized with a jet mill in a nitrogen stream to produce fine powder with an average particle size of 2.4 μm. Next, the fine powder was filled into the mold of a molding machine in an inert gas atmosphere, and while being oriented in a magnetic field of 15 kOe (=1.19 MA / m), it was subjected to a magnetic field of 0.6 Ton / cm in the direction perpendicular to the magnetic field. 2 The obtained powder compact was sintered in an Ar gas atmosphere at 1130°C for 3 hours, then cooled to room temperature at a cooling rate of 13°C / min, removed, and further subjected to heat treatment at 480°C for 1 hour in an Ar gas atmosphere as an aging treatment to obtain a sintered sample.

[0049] The obtained sintered body sample was analyzed by inductively coupled plasma optical emission spectrometry (ICP-OES) using a high-frequency inductively coupled plasma optical emission spectrometer (Hitachi High-Tech Science Corporation, SPS3520UV-DD). The composition was found to be Sm 10.9 Fe bal. Co 5.4 V 14.2 From the X-ray diffraction measurement of the powder obtained by crushing a part of the sample, the crystal structure of the main phase was found to be ThMn 12It was confirmed that the sintered body was of the type. In addition, an EPMA device (JXA-8500F, manufactured by JEOL Ltd.) was used to observe the structure of the sintered body and analyze the composition of each phase, and it was confirmed that the R-rich phase and the R(Fe,Co)2 phase were present at the grain boundaries at 1% by volume or more. The volume ratio of each phase was calculated as being equal to the area ratio in the backscattered electron image. R2(Fe,Co,M) 17 Phase, R3 (Fe, Co, M) 29 No α-Fe phase or α-Fe phase was observed. However, because oxides and other phases are also present, the total phase ratio is less than 100%. Based on the analysis value of the R(Fe,Co)2 phase, an alloy of the same composition was prepared by arc melting and homogenized at 830°C for 10 hours. Magnetization-temperature measurements were performed using a VSM, and the Curie temperature T c was 366°C.

[0050] The average crystal grain size of the main phase calculated from the results of etching and observing the sintered sample was 8.2 μm. Furthermore, when the magnetic properties were measured with a BH tracer, the room temperature coercivity H cJ The value was 10.3 kOe. cJ The temperature coefficient β was -0.44% / K. The results are shown in Tables 1 to 3.

[0051] [Comparative Example 1] The composition was adjusted using Sm metal, electrolytic iron, Co metal, and Ti metal, and the alloy strip was produced by melting in an Ar gas atmosphere using a high-frequency induction furnace and then strip-casting on a water-cooled Cu roll. The average crystal grain size in the minor axis direction of the alloy was 4.7 μm, as determined from an image observed with a laser microscope. The alloy was crushed and molded in a magnetic field in the same manner as in Example 1, sintered at 1170° C. for 3 hours in an Ar gas atmosphere, cooled to room temperature at a cooling rate of 13° C. / min, and further heat-treated at 480° C. for 1 hour in an Ar gas atmosphere, to obtain a sintered body sample of Comparative Example 1. The composition value of this sintered body sample analyzed by ICP method was Sm 10.7 Fe bal. Co 5.2 Ti 8.0 In addition, X-ray diffraction measurements revealed that the main phase of this sintered sample was ThMn 12It was confirmed that the sintered body was a type crystal. When the formed phase was examined by EPMA, it was found that the R(Fe,Co)2 phase was present, but the R-rich phase was not formed, and a fine (Fe,Co)2Ti phase was precipitated. Furthermore, the average crystal grain size of the main phase calculated in the same manner as in Example 1 was 8.8 μm. This sintered body sample showed a low coercive force of only 0.1 kOe at room temperature. The results are shown in Tables 1 to 3.

[0052] [Example 2] The composition was adjusted using Sm metal, electrolytic iron, ferrovanadium, Al metal, and Si, and the alloy was melted in an Ar gas atmosphere using a high-frequency induction furnace to produce a cast alloy. The alloy was heat-treated at 900°C for 50 hours to eliminate the primary crystal α-Fe. The structure of the alloy obtained was observed using a laser microscope, and the observed images confirmed that the average crystal grain size of the main phase was 5 μm or more. The alloy was subjected to hydrogen absorption treatment and dehydrogenation treatment by heating in a vacuum at 400°C to produce coarse powder, and then pulverized in a jet mill in a nitrogen gas flow to produce fine powder with an average grain size of 1.8 μm. The fine powder was then filled into a mold of a molding device in an inert gas atmosphere and molded in a magnetic field. The powder compact was sintered at 1140°C for 3 hours in an Ar gas atmosphere, and then cooled to room temperature at a cooling rate of 13°C / min to obtain a sintered sample.

[0053] The composition of the sintered body analyzed by ICP method was Sm 9.6 Fe bal. V 14.4 Al 0.4 S 0.2 In addition, X-ray diffraction revealed that ThMn 12 It was confirmed that the R-type crystal was the main phase. The R-rich phase and the R(Fe,Co)2 phase each existed at 1% by volume or more in the grain boundary of the sintered body structure. cJ is 8.3 kOe, and H cJ The temperature coefficient β of the R(Fe,Co) phase was -0.46% / K. Furthermore, the average crystal grain size of the main phase, calculated in the same manner as in Example 1, was 9.5 μm. Based on the analysis value of the R(Fe,Co) phase, an alloy of the same composition was prepared by arc melting and homogenized at 850°C for 20 hours. After that, magnetization-temperature measurements were performed using a VSM. The Curie temperature T cThe temperature was 349° C. The results are shown in Tables 1 to 3.

[0054] [Examples 3 to 9] As in Example 2, the composition was adjusted and a cast alloy was produced by high-frequency melting. In order to eliminate the primary crystal α-Fe, the alloy was subjected to heat treatment at 850 to 1100°C for 10 to 50 hours. The structure of the obtained alloy was observed by a laser microscope, and it was confirmed from the observed images that the main phase average crystal grain size was 1 μm or more in all cases. After performing hydrogen absorption treatment and dehydrogenation treatment by heating in a vacuum at 400°C to obtain coarse powder, the alloy was pulverized by a jet mill in a nitrogen gas flow to produce fine powder with an average grain size of 2 to 4 μm. The fine powder was further filled into a mold of a molding device in an inert gas atmosphere and molded in a magnetic field. This powder compact was sintered in an Ar gas atmosphere, cooled to room temperature, and further subjected to aging heat treatment to obtain a sintered body sample. Table 1 shows the composition of each sample analyzed by ICP method, the crystal structure of the main phase confirmed by X-ray diffraction, and the main phase average crystal grain size of the sintered body. Table 2 shows the sintering treatment conditions, cooling rate after sintering, aging treatment conditions, and B measured at room temperature for each Example. r , H cJ , and H cJ The temperature coefficient β of the sintering temperature is shown in Table 3. In Examples 7 and 8, a two-stage sintering method was applied in which the temperature was raised to the first sintering temperature, and then immediately lowered to the second sintering temperature and held for a predetermined time. Table 3 shows the composition and phase ratio of each phase analyzed by EPMA. In all of the samples in Examples 3 to 8, an R-rich phase and an R(Fe,Co)2 phase were formed in the grain boundary portion, and the samples showed a coercive force of 5 kOe or more at room temperature and a temperature coefficient β of -0.5% / K or more.

[0055] [Comparative Examples 2 to 6] Sintered body samples of Comparative Examples 2 to 5 were prepared in the same manner as in Example 2, except that the composition was adjusted to that shown in Table 1. The results are shown in Tables 1, 2, and 4. In Comparative Example 2, the total amount of R was less than 7 atomic %, and the sintering was not sufficient, and a large amount of α-Fe phase was formed in the sintered body. In Comparative Example 3, the total amount of R exceeded 15 atomic %, and the volume ratio of the main phase was less than 80%. In Comparative Example 4, the total amount of M element exceeded 20 atomic %, and no R-rich phase was observed, and an RFeSi phase of a PbClF type crystal was formed. In Comparative Example 5, an RCu2 phase of a KHg2 type crystal was present at the grain boundary triple junction, but the total amount of M element exceeded 20 atomic %, and no R-rich phase was found. In Comparative Example 6, the total amount of M was less than 4 atomic %, and ThMn 12 No Th2Zn type crystals were observed. 17 The main phase of the type crystal was formed.

[0056] [Comparative Example 7] The composition was adjusted using Sm metal, electrolytic iron, Ti metal, and V metal, and the raw material molten metal was cooled on a Cu roll rotating at a peripheral speed of 20 m / sec to produce a quenched ribbon raw material alloy. The ribbon had a thickness of 10 to 50 μm, and the alloy structure obtained was observed using a laser microscope. From the observed images, it was confirmed that the average crystal grain size was at least smaller than 1 μm, although it was too fine to measure. This alloy ribbon was pulverized in a ball mill, and then powder with a grain size of 300 μm or less was selected using a sieve and hot pressed at 750°C in an Ar atmosphere. The average crystal grain size of the main phase grains was as small as 0.2 to 0.3 μm, and the composition of the main phase and grain boundary phase could not be identified by EPMA. In addition, the easy axis of magnetization of the main phase was not aligned, so the low B r The results are shown in Tables 1, 2, and 4.

[0057] [Example 10] The composition was adjusted using Ce metal, electrolytic iron, Co metal, V metal, pure Si, and sponge titanium, and the composition was melted in an Ar gas atmosphere using a high-frequency induction furnace, and then strip-cast on a water-cooled Cu roll to produce a quenched ribbon alloy with a composition of Ce 8 atomic %, Co 1.2 atomic %, V 12 atomic %, Si 2.6 atomic %, Ti 0.8 atomic %, and the balance Fe. The average crystal grain size in the short axis direction of the alloy obtained from an image observed with a laser microscope was 4.5 μm. This alloy was subjected to hydrogen absorption treatment at room temperature, and then subjected to dehydrogenation treatment by heating at 400 ° C in a vacuum to obtain a coarse powder (this is referred to as the actual 10A powder). On the other hand, an alloy ingot with a composition of Sm 35 atomic % and the balance Fe was produced using Sm metal and electrolytic iron as raw materials using a high-frequency induction furnace, and was mechanically crushed to obtain a coarse powder (referred to as the actual 10B powder). The powders Actual 10A and Actual 10B were mixed in a weight ratio of 92:8, and then pulverized in a jet mill in a nitrogen stream to produce fine powder with an average particle size of 2.4 μm.

[0058] This mixed powder was subjected to magnetic field molding in the same manner as in Example 1, sintered in an Ar gas atmosphere at 980°C for 3 hours, cooled to room temperature at a cooling rate of 10°C / min, and further heat-treated in an Ar gas atmosphere at 480°C for 1 hour to obtain a sintered body of Example 10. The composition of the sintered body sample was Sm 2.8 Ce 7.5 Fe bal. Co 1.5 V 11.1 S 2.4 Ti 0.8 In addition, X-ray diffraction measurements showed that the main phase of this sintered body was ThMn 12 The composition of the main phase measured by EPMA was Ce in the center of the grain. 7.8 Fe bal. Co 1.4 V 11.7 S 2.3 Ti 0.9 does not contain Sm, but the outer shell of the grains does not contain Sm 5.1 Ce 2.7 Fe bal. Co 1.5 V 11.6 S 2.5 Ti 0.8It was confirmed that the Sm / R ratio in the grain interior was lower than that in the surface layer. The compositional analysis values ​​of the R-rich phase and the R(Fe,Co)2 phase were Sm 27.7 Ce 52.4 Fe bal. Co 1.1 V 0.1 , Sm 12.6 Ce 20.4 Fe bal. Co 0.6 V 0.8 S 0.1 It was confirmed that the Sm / R ratio inside the grains was lower than that of the R-rich phase and the R(Fe,Co)2 phase. The average crystal grain size of the main phase was 8.6 μm. The coercive force of this sintered body was 10.3 kOe at room temperature, and the temperature coefficient of coercive force β was -0.44% / K. The Curie temperature T c was 118°C.

[0059] [Example 11] The composition was adjusted using Nd metal, electrolytic iron, Co metal, V metal, Al metal, and W metal, and the alloy strip was melted in an Ar gas atmosphere using a high-frequency induction furnace, and then strip-cast on a water-cooled Cu roll to produce an alloy strip with a thickness of about 0.2 to 0.4 mm. The average grain boundary phase spacing of this alloy was calculated to be 2.9 μm. The alloy was subjected to hydrogen absorption treatment at room temperature, and then subjected to dehydrogenation treatment by heating in a vacuum at 400 ° C to produce coarse powder, which was then pulverized in a jet mill in a nitrogen gas flow to produce fine powder with an average particle size of 1.9 μm. Next, the fine powder was pressure-molded while being oriented in a magnetic field, sintered in a vacuum at 1170 ° C for 3 hours, cooled to room temperature at a cooling rate of 12 ° C / min, and taken out to obtain a sintered body.

[0060] Next, Sm metal, Co metal and Al metal were used as raw materials, and placed in a quartz tube with a nozzle hole of 0.5 mm, melted by high-frequency induction in an Ar atmosphere, and then sprayed onto a Cu roll rotating at a peripheral speed of 25 m / s to produce a quenched ribbon alloy with a composition of Sm 75 atomic %, Al 5 atomic %, and the remainder Co. The quenched ribbon was then pulverized by a ball mill for 30 minutes to produce a powder with a mass median particle size of 10.3 μm. The above sintered body was immersed in a liquid in which this powder and ethanol were mixed and stirred in a weight ratio of 1:3, and then pulled up, dried with hot air, and the powder was applied to the surface of the sintered body. These were subjected to a diffusion heat treatment at 880 ° C. in a vacuum for 10 hours, and further to an aging heat treatment at 500 ° C. in an Ar gas atmosphere for 2 hours, to obtain a sintered body of Example 11.

[0061] The sintered body sample of Example 11 was subjected to ICP analysis, and the composition was Sm 1.4 Nd 9.6 Fe bal. Co 9.7 V 13.0 Al 0.6 W 0.6 From the X-ray diffraction measurement of the powder obtained by crushing a part of the sample, the crystal structure of the main phase was found to be ThMn 12 In addition, the structure of the sintered body was observed by EPMA and the composition of each phase was analyzed, and it was confirmed that the R-rich phase and the R(Fe,Co)2 phase existed at the grain boundaries at 1% by volume or more. R2(Fe,Co,M) 17 Phase, R3 (Fe, Co, M) 29 No α-Fe or α-Fe phase was observed. Note that the total of the phase ratios is less than 100% because oxides and other phases are also present.

[0062] The compositional analysis values ​​of the center and outer periphery of the main phase grains by EPMA were Nd 7.7 Fe bal. Co 9.8 V 13.8 Al 0.6 W 0.6 , Sm 3.7 Nd 4.0 Fe bal. Co 9.9 V 13.7 Al 0.6 W 0.4It was confirmed that the Sm / R ratio inside the grains was lower than that of the outer crust. The compositional analysis values ​​of the R-rich phase and the R(Fe,Co)2 phase were Sm 26.7 Nd 52.1 Fe bal. Co 17.4 V 0.4 Al 0.7 , Sm 12.3 Nd 22.3 Fe bal. Co 4.1 V 0.1 Al 0.3 While no Sm was detected inside the main phase grains, the R-rich phase and R(Fe,Co)2 phase present at the grain boundaries contained Sm, and it was confirmed that the Sm / R ratio was high.

[0063] Based on the analysis value of the R(Fe,Co)2 phase, an alloy with the same composition was prepared by arc melting and homogenized at 800℃ for 20 hours. After that, magnetization-temperature measurements were performed using a VSM. The Curie temperature T c The average crystal grain size of the main phase calculated from the results of etching and observing the sintered body of Example 18 was 9.0 μm. Furthermore, when the magnetic properties were measured with a BH tracer, the room temperature coercivity H cJ The value was 8.8 kOe. cJ The temperature coefficient β was -0.45% / K.

[0064] [Comparative Example 8] The sintered body of Comparative Example 9 was produced in the same manner as the sintered body of Example 11, except that the sintered body was not subjected to powder coating or diffusion heat treatment, but was subjected to aging heat treatment at 500°C for 2 hours in an Ar gas atmosphere.

[0065] The composition of the sintered body of Comparative Example 8 is Nd 9.5 Fe bal. Co 10.1 V 12.3 Al 0.4 W 0.5 The compositional analysis values ​​of the center of the main phase grain and the R(Fe,Co)2 phase were Nd 7.9 Fe bal. Co 10.4 V 12.8 Al0.4 W 0.5 , Nd 32.3 Fe bal. Co 4.5 V 0.2 Al 0.1 The room temperature coercivity H cJ The result was 0.1 kOe. The results are shown in Tables 5 to 7. The results are shown in Tables 5 to 7.

[0066] [Table 1]

[0067] [Table 2]

[0068] [Table 3]

[0069] [Table 4]

[0070] [Table 5]

[0071] [Table 6]

[0072] [Table 7]

Claims

1. The composition has the formula (R 1-a Zr a ) x (Fe 1-b Co b ) 100-x-y (M 1 1-c M 2 c ) y (R is a combination of Sm and one or more elements selected from Sc, Y, La, Ce, Pr, Nd, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu; M 1 represents one or more elements selected from the group consisting of V, Cr, Mn, Ni, Cu, Zn, Ga, Al, and Si; M 2 is one or more elements selected from the group consisting of Ti, Nb, Mo, Hf, Ta, and W, and x, y, a, b, and c are each represented by 7≦x≦15 atomic %, 4≦y≦20 atomic %, 0≦a≦0.2, 0≦b≦0.5, and 0≦c≦0.9, respectively; 12 The main phase is composed of a compound of a Fe-type crystal in an amount of 80% by volume or more, and the average crystal grain size of the main phase is 1 μm or more. 2 phase at grain boundaries, The Sm / R ratio in the interior of the grains of the main phase is R-rich phase and R(Fe, Co) 2 The anisotropic rare earth sintered magnet is characterized in that the Sm / R ratio of the magnet is lower than that of the magnet.

2. The R-rich phase and R(Fe, Co) 2 2. The anisotropic rare earth sintered magnet according to claim 1, characterized in that the phases are contained in a total amount of 1 volume % or more.

3. 3. The anisotropic rare earth sintered magnet according to claim 1, wherein the R-rich phase contains 40 atomic % or more of R.

4. The R(Fe, Co) 2 4. The anisotropic rare earth sintered magnet according to claim 1, wherein the phase exhibits ferromagnetism or ferrimagnetism at room temperature or above.

5. 5. The anisotropic rare earth sintered magnet according to claim 1, wherein the Sm / R ratio inside the main phase grain is lower than the Sm / R ratio in the outer periphery of the main phase grain.

6. 6. The anisotropic rare earth sintered magnet according to claim 1, wherein the main phase grains do not contain Sm inside.

7. 7. The anisotropic rare earth sintered magnet according to claim 1, which exhibits a coercive force of 5 kOe or more at room temperature and a temperature coefficient β of coercive force of -0.5% / K or more.

8. ThMn 12 The method for producing an anisotropic rare earth sintered magnet according to any one of claims 1 to 7, characterized in that an alloy containing a compound phase of the type crystal is pulverized, compacted under application of a magnetic field to form a green body, and then sintered at a temperature of 800°C or higher and 1400°C or lower.

9. ThMn 12 9. The method for producing an anisotropic rare earth sintered magnet according to claim 8, characterized in that an alloy containing a compound phase of the type crystal and an alloy having a higher R composition ratio and Sm / R ratio than those of the type crystal are pulverized and mixed, and then compacted in an applied magnetic field to form a green body.

10. ThMn 12 10. The method for producing an anisotropic rare earth sintered magnet according to claim 8, wherein a material containing Sm is brought into contact with a sintered body having a compound phase of the type crystal as a main phase, and the material is heat-treated at a temperature of 600°C or higher and lower than the sintering temperature, thereby diffusing Sm into the sintered body.

11. 11. The method for producing an anisotropic rare earth sintered magnet according to claim 10, characterized in that the material containing Sm that is brought into contact with the sintered body is one or more selected from the group consisting of Sm metal, an Sm-containing alloy, a compound containing Sm, and vapor containing Sm, and is in the form of one or more selected from the group consisting of powder, thin film, ribbon, foil, and gas.

12. The method for producing an anisotropic rare earth sintered magnet according to any one of claims 8 to 11, characterized in that the sintered body is subjected to a heat treatment at a temperature of 300 to 900°C.

Citation Information

Patent Citations

  • Rare earth permanent magnet

    JP1992322406A

  • Rare earth permanent magnet

    JP1994231920A

  • Permanent magnet

    JP2001189206A

  • Rare earth magnet

    JP2017112300A

  • Alloy for rare earth magnet

    JP2019044259A

Cited By

  • Anisotropic rare earth sintered magnet and method for producing same

    JPWO2021193334A1